2009
DOI: 10.1038/bmt.2008.398
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic activity of NK cell clones against acute childhood precursor-B-cell leukaemia is influenced by HLA class I expression on blasts and the differential KIR phenotype of NK clones

Abstract: Relapse after allo-SCT in patients with acute leukaemia remains a major problem. A beneficial impact of alloreactive natural killer (NK) cells has been reported for myeloid malignancies, but has been questionable for B-lineage ALL. We analysed lysis of primary paediatric precursor-B-ALL blasts by 285 NK cell clones to investigate whether HLA class I expression on the blasts and phenotypic killer cell Ig-like receptor (KIR) expression on NK cells affect the lytic activity against ALL blasts. Precursor-B-ALL bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…In the absence of a KIR-ligand mismatch, NK cells are capable of killing leukemic blasts with low expression of HLA class I molecules more efficiently than cells with high HLA class I expression. 29,30 Indeed, our analysis of HLA class I expression on primary blasts from patients with acute lymphoblastic leukemia 31 or AML (supplemental Figure 4) showed significantly lower expression on leukemic blasts compared with cells from healthy donors. Thus, we propose that in a setting where cancer cells downregulate HLA class I molecules, the licensing status of NK cells and coexpression of activating KIRs will be the major determinants of alloreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a KIR-ligand mismatch, NK cells are capable of killing leukemic blasts with low expression of HLA class I molecules more efficiently than cells with high HLA class I expression. 29,30 Indeed, our analysis of HLA class I expression on primary blasts from patients with acute lymphoblastic leukemia 31 or AML (supplemental Figure 4) showed significantly lower expression on leukemic blasts compared with cells from healthy donors. Thus, we propose that in a setting where cancer cells downregulate HLA class I molecules, the licensing status of NK cells and coexpression of activating KIRs will be the major determinants of alloreactivity.…”
Section: Discussionmentioning
confidence: 99%
“…24 NK clones positive for NKG2A and negative for CD158a, b and e showed strong lysis of pediatric blasts with reduced HLA-expression indicating that NKG2A-HLA-E interaction may not be the main inhibiting signal in these target cells. 25 However, the lysis of neuroblastoma and acute lymphoblastic leukemia blasts mediated by reconstituting NK cells could be clearly improved by antibody dependent cellular cytotoxicity using appropriate antibodies. We used optimized chimeric antibodies against CD19 for antibody dependent cellular cytotoxicity in acute lymphoblastic leukemia blasts and against GD2 in neuroblastoma and found a significant increase in specific lysis both by resting and IL-2 activated NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…24 In line with this, our group earlier demonstrated that the in vitro cytolytic activity of NK cells against BCP-ALL in part correlated with the extent of major histocompatibility complex expression on the respective specimen. 6,7 Per our previous work, which demonstrated that the injection of patient-specific leukemia into NSG mice resulted in the constitution of a model that reflected individual leukemogenecity, 9 we analyzed the leukemic burden in BCP-ALL-bearing mice upon adoptive NKcell transfer and demonstrated that KIR-KIRL mismatched NK cells targeted, but did not eliminate, pediatric BCP-ALL. Mechanistically, the interaction of NK cells with BCP-ALL was accompanied by a heightened functionality of alloreactive KIR 1 NK cells of KIR-KIRL mismatched donors, particularly in terms of their ability for degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data indicate that the disease entity of pediatric BCP-ALL might yet be a target of "alloreactive" NK cells. 1,2,[6][7][8] Considering the various potential facets of NK-cell immune therapy, such as adoptive transfer of mature NK cells, co-transfer of mature NK cells during graft manipulation, emergence of immature NK cells early posttransplantation, and the currently existing limited number of clinical studies in BCP-ALL-bearing children, we sought to define conditions under which NK-cell-mediated alloreactivity toward pediatric BCP-ALL could be fully exploited.…”
Section: Introductionmentioning
confidence: 99%